2020
DOI: 10.1186/s12935-020-1132-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-4316 inhibits gastric cancer proliferation and migration via directly targeting VEGF-A

Abstract: Background and aims: microRNAs (miRNAs) have been reported to regulate proliferation and migration by downregulating the expression of target genes. The aims of this study were to investigate whether miR-4316 inhibited proliferation and migration by downregulating vascular endothelial growth factor A (VEGF-A) and its clinical significance in gastric cancer (GC). Methods: The clinical tissues of the GC patients for miR-4316 and VEGF-A were detected by qRT-PCR. The protein levels of VEGF-A and c-Met were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The classic mechanism for miRNA was modulate target genes by binding on its complementary binding sites of mRNA 3′-UTR, inhibiting target mRNA translating or promoting mRNA degradation. In this study, we confirmed that VEGFA may serve as a functional target of miR-4316, which has been proved to have inhibitory effects on proliferation and migration (Mousa et al, 2020). Therefore, we suspected that VEGFA is one of the miR-4316 target genes in LUAD cells.…”
Section: Discussionsupporting
confidence: 73%
“…The classic mechanism for miRNA was modulate target genes by binding on its complementary binding sites of mRNA 3′-UTR, inhibiting target mRNA translating or promoting mRNA degradation. In this study, we confirmed that VEGFA may serve as a functional target of miR-4316, which has been proved to have inhibitory effects on proliferation and migration (Mousa et al, 2020). Therefore, we suspected that VEGFA is one of the miR-4316 target genes in LUAD cells.…”
Section: Discussionsupporting
confidence: 73%
“…With the development of molecular biology, an increasing number of biomarkers, such as miRNAs, that play roles in the progression of cancers and tumors have been identified, and the therapy of different cancers, including OS, has improved rapidly (23)(24)(25). miRNAs have been reported to play vital biomarker roles in various cancers, such as lung cancer, ovarian cancer, breast cancer, and gastric cancer (11,(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of RASSF8 promoted the transcriptional activity of NF-κB and p65 translocation. Mousa et al [ 66 ] showed that miR-4316 inhibited vascular endothelial growth factor A (VEGF-A) expression and induced the suppression of migration and colony formation in tumor cell lines. β-Elemene extracted from Chinese herbal medicine showed a good effect on the inhibition of metastasis in nude mice.…”
Section: Invasion and Metastasismentioning
confidence: 99%